Construção e validação do conteúdo da escala de avaliação de habilidades da natação - Borges, Cristiany de Carvalho (Universidade Federal de São Carlos, 2022)
As chronological age increases, people become less active and their functional capacity de-creases, contributing to reduced independence. In this sense, swimming as a physical exercise is presented as a health-promoting strategy, since it can be practiced at any age and brings multiple benefits. The scarcity of instruments that evaluate the processes of acquisition of aquatic skills makes it difficult to monitor the evolution of students in practice. In view of the above, the objective of the study is to develop and validate the content of the Swimming Skills Assessment Scale. For this, three steps were performed: the first with the objective of describing the processes of elaboration and construction of the scale; the second to analyze its content from the perspective of 10 expert judges; and the third to analyze the judges' return and adjust the scale. This is a methodological study, involving a qualitative and quantitative approach to research. To evaluate the levels of agreement between the expert judges on each of the component items of the instrument, the Content Validity Index (CVI) was calculated. The results of the present study revealed a total CVI for the instrument of 0.96, indicating that the scale of swimming skills as an evaluation process in swimming learning presents objec-tivity, clarity and reliability in its content. Suggests for future studies to carry out the applica-tion study of the Swimming Skills Assessment Scale among the elderly and populations with other age groups.
Construction and validation of the content of the swimming skills assessment scale
Keywords: Construção; Validação de instrumento; Natação; Pessoas idosas; Habilidades aquáticas; Habilidades motoras; CIENCIAS DA SAUDE::EDUCACAO FISICA